Analisis Penerapan Social Media Marketing di Lafera Space Pekanbaru - Syarifah Serfika; Meyzi Heriyanto (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Lafera Space is a coffee shop located in Bangau Sakti, Pekanbaru. This study aims to obtain clear information and insights into the implementation of social media marketing strategies at Lafera Space Pekanbaru. The research approach used is a descriptive qualitative method that describes how Lafera Space conducts social media marketing. Data collection was conducted through interviews with seven informants, documentation study, literature review, and data source triangulation. The research findings indicate that the implementation of the dimensions of context, communication, and collaboration in social media marketing at this coffee shop is already well-established. However, for the dimension of connection, consumers still perceive some challenges that need to be addressed and improved by Lafera Space Pekanbaru